ENHANCING STUDENTS’ COMMUNICATIVE COMPETENCE THROUGH DAILY LANGUAGE ACTIVITIES - Meita Lesmiaty Khasyar (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2020)
There are two main competences that should be developed during the language learning process, Grammatical Competence and Communicative Competence. The former deals with the ability to generate and construct some types of grammatical sentences, while the latter is the actual use of language in a real situation, and in various kinds of language use in different context. Once the students can master the rules of sentence structure, but they are not sucessful at being able to use the language in menaingful communication. For those reasons, the language teacher should design the learning process that encourage their student to speak and communicate actively. Daily language activities is one way which is hoped that both competences, especially the communicative competence can be reached in foreign language learning. The students, then, understand how to vary the language use according to the setting and their purpose to speak. This qualitative research aimed to describe the language teaching model through daily language activities implemented in Pesantren, in order to help the students master the communicative competence well. In collecting the data the researcher used observation and indepth interview to know the real condition of the teaching method and strategies used by Pesantren in teaching the foreign language, and some factors affecting the success of language teaching. Finally, the findings showed that the daily language activities can improve the students’ communicative competence.